UPAYA PENGEMBANGAN KARAKTER DAN PENGUATAN MODERASI BERAGAMA DALAM PERSPEKTIF TRI KAYA PARISUDHA DI SMA NEGERI 10 LUWU TIMUR, KABUPATEN LUWU TIMUR, SULAWESI SELATAN - Kurniawan, Ketut Citra; Ni Wayan Anggi Yudiantari; Ni Komang Sutriyanti (Guna Widya: Jurnal Pendidikan Hindu, 2025)
Character development and strengthening religious moderation are very important in the current era. Education is a determinant in producing pioneers who will carry the ideals and future of a nation. Especially in Indonesia, with its diverse societal climate, it is not an easy challenge to realize Harmony in Diversity. Moreover, religion is a crucial thing in Indonesia. Moral degradation is something that cannot be avoided in this era, especially among students who are in the phase of searching for identity. So, character development and strengthening religious moderation through the Tri Center for Education are very necessary, especially in the school environment which has a strategic role in forming students who has a moral responsibility to be a true and proper human being and a desirable member of society. This research is interested in studying Tri Kaya Parisudha's perspective in efforts to develop character and strengthen religious moderation at SMA Negeri 10 East of Luwu and examine the relationship between Tri Kaya Parisudha, the nine key words for religious moderation and the verses contained in the sacred Vedic literature.